Day 2 Thu, September 06, 2018 2018
DOI: 10.2118/191799-ms
|View full text |Cite
|
Sign up to set email alerts
|

Time Dependent Depletion of Parent Well and Impact on Well Spacing in the Wolfcamp Delaware Basin

Abstract: Parent-child relationship is becoming a topic of high interest in the Permian Basin as more infill wells are being drilled at various times after the parent well has been produced. This paper uses an advanced modelling workflow to determine the impact of parent depletion on infill well spacing at various periods of the parent well production. As the parent well is being produced, constant well spacing based on virgin condition becomes problematic because pressure depletion around the well leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…There is no simple formula to guide proport well spacing in the Permian Basin. Defeu et al [24], considering data from Wolfcamp shale play in the Delaware Basin, one study found that when a child well was drilled within 1,000 feet of an older well, the parent outperformed the new child by 66%. When the comparison was adjusted for high-intensity completions with higher fluid and proppant volumes, 79% of older Wolfcamp wells performed better than offset child wells.…”
Section: Recent Advancements In Well Spacingmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no simple formula to guide proport well spacing in the Permian Basin. Defeu et al [24], considering data from Wolfcamp shale play in the Delaware Basin, one study found that when a child well was drilled within 1,000 feet of an older well, the parent outperformed the new child by 66%. When the comparison was adjusted for high-intensity completions with higher fluid and proppant volumes, 79% of older Wolfcamp wells performed better than offset child wells.…”
Section: Recent Advancements In Well Spacingmentioning
confidence: 99%
“…It is well known in the industry that an increase in well spacing lowers the wells EUR [24]. The wider the spacing the higher the EUR per well to a point, but production per section (lease) drops as fewer wells are drilled to drain the section.…”
Section: Recent Advancements In Well Spacingmentioning
confidence: 99%
“…Recently, there has been a surge in developing and proposing new models to characterize the parent-child well fracture interference in unconventional reservoirs [28,29]. The "parent wells" are already-existing production wells, while the "child wells" are the new infill wells that have just been stimulated through hydraulic fracturing.…”
Section: Governing Mathematical Modelsmentioning
confidence: 99%